Identification of Visual Contamination in Khalidiya City Using Quantitative Analysis Methods (Journal of University of Babylon for Engineering Sciences, 2018)
The study dealt with one of the types of environmental pollution, which is visual pollution as it affects the city without other human stable. The field study was based on the detection of the causes of visual pollution in the city of Khalidiya and the biological and psychological effects on the population. It was found that the city suffers from visual pollution due to economic, social, political, planning and legal reasons. The questionnaire was distributed by 5% distributed to the population, as well as the use of modern quantitative methods (s.p.s.s), which revealed five types of pollution, Residential areas between very severe pollution and very weak depending on the size of the population and their economic and social level in the city.